2021
DOI: 10.1073/pnas.2023757118
|View full text |Cite
|
Sign up to set email alerts
|

Observing the subglacial hydrology network and its dynamics with a dense seismic array

Abstract: Subglacial water flow strongly modulates glacier basal motion, which itself strongly influences the contributions of glaciers and ice sheets to sea level rise. However, our understanding of when and where subglacial water flow enhances or impedes glacier flow is limited due to the paucity of direct observations of subglacial drainage characteristics. Here, we demonstrate that dense seismic array observations combined with an innovative systematic seismic source location technique allows the retrieval of a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…This evolution was identified by Nanni, Gimbert, et al. (2021) as a transition from a distributed to a more localized drainage system in response to an increase in surface melt, consistent with expectations based on numerous observational and numerical studies in different contexts (Irarrazaval et al., 2021; Lewington et al., 2020; Tranter et al., 1996; Vincent & Moreau, 2016).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This evolution was identified by Nanni, Gimbert, et al. (2021) as a transition from a distributed to a more localized drainage system in response to an increase in surface melt, consistent with expectations based on numerous observational and numerical studies in different contexts (Irarrazaval et al., 2021; Lewington et al., 2020; Tranter et al., 1996; Vincent & Moreau, 2016).…”
Section: Resultssupporting
confidence: 85%
“…At high frequencies ((10–20) Hz), short and repeated pulses mainly composed of surface waves (phase velocity ∼1,590 m. sec −1 ) cross the entire array and dominate the seismic signal with a few seconds recurrence time (Gimbert et al., 2021). At low frequency ((3–7) Hz), subglacial water flow has been observed to generate continuous seismic noise (Nanni, Gimbert, Vincent et al., 2020) and a dynamic mapping of subglacial hydrological flows was carried out via the study of spatially dispersed seismic sources generating low phase coherence (Nanni, Gimbert, et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding observational scales of subglacial hydrology is vital to predicting how Measurement of glaciohydraulic tremor, the continuous seismic signal generated by turbulent water flow in a glacier, can improve the spatial and temporal scales of subglacial hydrological observations. By adapting theoretical descriptions of tremor generation from fluvial seismology (Burtin et al 2008, Burtin et al 2011, Tsai et al 2012, Schmandt et al 2013, Gimbert et al 2014, glaciohydraulic tremor has already been shown to reveal properties of subglacial hydrologic systems such as water flux (Bartholomaus et al 2015, Winberry et al 2009, sediment transport (Gimbert et al 2016), water pressurization (Gimbert et al 2016, Lindner et al 2020, Nanni et al 2020, water flow source location (Vore et al 2019, Nanni et al 2021, and flood front propagation (Eibl et al 2020). In addition, analysis of tremor signals at glaciers can also be interpreted to locate and describe other glaciohydraulic sources such as moulin activity (Aso et al 2017, Röösli et al 2014, Röösli et al 2016, Lindner et al 2020) and crack waves in the basal water layer (Gräff et al 2019).…”
Section: Introductionmentioning
confidence: 99%